Rate of torque development in hip muscles of women with and without patellofemoral pain - Caetano, Beatriz Signori [UNESP]; Araujo, Isabela Vitoria Souza [UNESP]; Cipolli, Jamilly Radiuc [UNESP]; Cruz, Ana Carla Ballielo [UNESP]; Spinoso, Deborah Hebling [UNESP] (Elsevier, 2025)
Background Patellofemoral pain (PFP) is a common musculoskeletal disorder, primarily affecting women. It is characterized by pain in the anterior region of the knee, which can lead to functional limitations in the knee and hip. The rate of torque development (RTD) is considered a more representative indicator of daily task performance compared to maximal strength. Even though previous studies have examined strength deficits in individuals with PFP, limited research has explored RTD alterations in the hip musculature of this population. Understanding its influence on the hip musculature in this population can contribute to a better understanding of the factors involving PFP. Objectives To compare the rate of torque development (RTD) of the hip extensor and abductor muscles in women with and without PFP. Methods This is a cross-sectional study involving 60 women, divided into two groups: PFP (n = 30) and control (n = 30). Hip extensor and abductor torque were measured using a System 4 PRO isokinetic dynamometer (Biodex®). The protocol consisted on three maximal concentric contractions and the movement range was 0° to 30° of abduction and 90° to 60° of hip flexion at an angular velocity of 30°/second. RTD was calculated by dividing the difference in normalized torque by the difference in time from contraction onset to 30% (RTD 30%) and 60% (RTD 60%) of maximum torque ([Nm.Kg?¹] × 100/ms). Data was statistically analyzed using PASW Statistics 18.0® (SPSS), applying the t-test. Results Women with PFP showed a reduction in the RTD of hip extensors and abductors at 30% (p < 0.001, p = 0.015, respectively) and 60% of peak torque (p < 0.001, p = 0.015, respectively) compared to asymptomatic women. Conclusion Women with PFP exhibit deficits in rate of torque development of the hip extensor and abductor muscles when compared to women without PFP, underscoring the importance of targeting various aspects of muscle function in exercise therapy. Implications RDT may better represent the ability to perform daily living activities compared to maximal strength. Everyday tasks require rapid force production, yet this deficit in muscle power is rarely addressed in exercise therapy. Therefore, it is essential to emphasize both hip strength and power in the rehabilitation of women with patellofemoral pain to achieve more favorable medium- and long-term outcomes.